REEF FISHES BIODIVERSITY IN MARINE SANCTUARY AT MINAHASA UTARA DISTRICT, NORTH SULAWESI - Fakhrizal Setiawan; Sonny Tasidjawa; Efra Wantah; Hendri Johanis (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
ABSTRACTThere are some marine sanctuaries (DPL) which are managed together by its societies in North Minahasa regency. From 19 villages with DPL, we conducted surveys using point intercept transect in 14 villages both inside and outside DPL in the subdistrict West Likupang and East Likupang, North Minahasa. Result showed that live coral cover was in general in moderate to excellent conditions both inside and outside DPL. Reef fish recorded in the study areas consisted of 267 reef fish species which categorized into 40 families. Bahoi village had the highest abundance and biomass within the DPL due to a very good condition of coral reef ecosystemn (>75% coral cover) both inside and outside DPL. Biomass of reef fish outside DPL of Bahoi was small but its abundance was the highest. This conditions indicated that the size of reef fish outside of Bahoi DPL was small and this gave a positive perspective to supply fishes into the outside region of Bahoi DPL. Overall, marine sanctuary in North Minahasa contained reef fish community structure in good condition, moderate diversity, relatively labile of evenness index, and low dominance. Grouping by similarity, reef fish species were generally similar in all locations. The separation of DPL locations produced some different fishes group due to its different location, oceanographic conditions, and characters. Keywords: Marine sanctuary, reef fish community, North Minahasa.